Prototyping essentials with Axure : a comprehensive strategy and planning guide for the production and world-class UX artifacts such as annotated wireframes, immersive prototypes, and detailed documentation /: a comprehensive strategy and planning guide for the production and world-class UX artifacts such as annotated wireframes, immersive prototypes, and detailed documentation. (2014) - Schwartz, Ezra; Srail, Elizabeth
No abstract available